2012
DOI: 10.1111/j.1365-2109.2012.03255.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incubation temperature on the embryonic development and yolk-sac larvae of the Pacific red snapperLutjanus peru(Nichols & Murphy, 1922)

Abstract: The effect of incubation temperature on embryonic development and yolk-sac larva of the Pacific red snapper Lutjanus peru were evaluated by testing the effect of 26, 28 and 30°C, as this is the natural thermal interval reported during the spawning season of Pacific red snapper in the Gulf of California, Mexico. Sixteen developmental stages were observed. The incubation temperature affected the rate of development and time to hatching, being shorter at 30 than at 26°C, but no significant effect (P < 0.05) on la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
1
11
1
7
Order By: Relevance
“…; Peña et al . ). For example, SL at hatching was inversely related to increasing temperature, being larger at lower temperatures than at higher ones (Blaxter ; Jordaan et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Peña et al . ). For example, SL at hatching was inversely related to increasing temperature, being larger at lower temperatures than at higher ones (Blaxter ; Jordaan et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Peña et al . ). Yolk‐sac consumption occurred earlier than for the oil globule at all experimental temperatures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, larviculture trials of Pacific red snapper have been characterized by very low survival at first feeding, with most trials leading to total mortality during the first week of development. Therefore, several aspects related to feeding and early development have been studied in the Unidad Piloto de Maricultivos del Centro Interdisciplinario de Ciencias Marinas del Instituto Politécnico Nacional (Mariculture Pilot Unit of the Interdisciplinary Center for Marine Science at the National Polytechnic Institute; CICIMAR‐IPN), including the effect of the incubation temperature on yolk‐sac larvae (Peña, Dumas, Zavala‐Leal & Contreras‐Olguín ), the feeding response under different culture conditions (Zavala‐Leal, Dumas, Peña, Contreras‐Olguín & Hernández‐Ceballos ) and larvae structural development at first feeding (Zavala‐Leal, Dumas, López‐Villegas, Peña, Contreras‐Olguín, Flores‐Montijo & De la Cruz‐Agüero ). However and as a result of the low survival rates under intensive culture conditions, larval development in this species has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…The effects on the environment formed by temperature and light quantity have been studied in a few aquatic species, such as sea bass (Barahona‐Fernandes, ; Bayarri, Madrid & Sánchez‐Vázquez, ; Copeland & Watanabe, ), greenback flounder (Hart & Purser, ), yellow perch (Martin, Wahl & Czesny, ), Pacific red snapper (Peña, Dumas, Zavala‐Leal & Contreras‐Olguín, ), European hake (Guevara‐Fletcher, Alvarez, Sanchez & Iglesias, ) and sablefish (Lee et al., ). It has been found that they play an important role on early ontogeny and larval growth/survival.…”
Section: Introductionmentioning
confidence: 99%